Subjective Precariousness and Recognition in the Work Trajectories of Seasonal Fruit Workers in Chile; [Precariedad Subjetiva y Reconocimiento en Las Trayectorias del Trabajo de Temporeras de la Fruta en Chile] - Margarit-Segura, D (Universidad de Talca, 2024)
The guiding question of the article is: How subjective labour precariousness is expressed in the individual and collective biographical trajectories of adult and national female seasonal fruit pickers in Chile? This includes understanding the biographies from work, personal and family perspectives. The methodology was qualitative, involving in-depth interviews with rural female fruit pickers in the regions of Maule and O Higgins. The analyzes focuses on the narratives of 10 Chilean workers with children, organized into 5 categories: 1) work trajectories and link with family itineraries; 2) trajectories crossed by caregiving; 3) invisibility and lack of recognition; 4) humiliation, grievance and discomfort; and 5) normalization of labor unprotection. We conclude that subjective precariousness is expressed in social grievance, perception of injustice and emotional discomfort, derived from experiences of precariousness in the objective working conditions - instability, piece-rate payment, stagnation of "deal" amounts, poor environmental and sanitary conditions, and hostility from management -thus, both dimensions -being and feeling- shape the fragile work experience. The lack of social recognition transcending the work sphere, adaptation as an expression of symbolic violence and reproductive overload, deepen the normalization of precariousness extended to all aspects of life. © 2024 Universidad de Talca. All rights reserved.